PENDIDIKAN DALAM PERSPEKTIF ISLAM DAN PERANANNYA DALAM MEMBINA KEPRIBADIAN ISLAMI - Tatang Hidayat; Ahmad Syamsu Rizal; Fahrudin Fahrudin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The presence of Islamic education is expected to be an alternative solution to educational problems caused by the materialism education system. This present study aims at investigating education from an Islamic perspective and its role in fostering Islamic personality. This study employed a qualitative approach and literature review method. Based on the results of the discussion, there has been no agreed term on education based on Islamic perspective. However, in this case, the writer is more inclined to ta'dÄb as the term for education in Islam since it, based on its conceptual structure, has included the elements of science (ilm), teaching (ta'lÄ«m), and good care (tarbiyaÄ§). The purposes of Islamic education are to develop an Islamic personality and to master Islamic safaqah, science and technology, and adequate expertise. In Islam, teachers are regarded as a highly honored person, and students are encouraged to maintain good character and conduct (adab) when they interact with their teachers. In addition, Islamic curriculum and education materials are supposed to be in line with the Islamic Aqeedah (faith). In principle, Islamic education methods have their own characteristics and one of them is the Quranic education method. All media and facilities are permissible as long as it does not conflict with the Islamic Aqeedah (faith). The evaluation in Islamic education consists of measurements and assessments covering the aspects of aqliyah, qolbiyah, and amÄliyah. Islamic education plays an important role in fostering Islamic personality since it is inseparable from the idea of Islamic education in order to foster an Islamic personality.